A Hybrid MCDM Model for Improving GIS-Based Solar Farms Site Selection - Chao-Rong Chen; Chi-Chen Huang; Hung-Jia Tsuei (International Journal of Photoenergy)
The purpose of this research is to establish a decision model for improving the performance of solar farms. To investigate the interdependent interrelationship and influential weights among criteria for solar farms site selection, a hybrid MCDM model including decision-making trial and evaluation laboratory (DEMATEL) and DEMATEL-based analytic network process (DANP) based on geographical information systems (GIS) is utilized. The empirical results display that there are interdependence and self-effect relationships among criteria via DEMATEL technique. According to the influential network relation map (INRM), the dimension that administrators of solar energy industry should improve first when enhancing the performance of solar farms is orography. In the ten criteria, solar radiation is the most important criterion impacting solar farms site selection, followed by average temperature and distance to villages.